Digital guidning på campus Alnarp - Edvardsson, Anna (2006)
Today digital guides are most frequently used by the museum and tourism industries. They are also used for education purposes. They make it possible to distribute information and have it easily accessible. In addition to written information they add sound, pictures and videos which lift the whole impression of the visited place to a higher level.